Sosialisasi Qris di Sektor Usaha Mikro: Pelatihan dan Dukungan Teknis untuk Pengusaha Lokal (Studi Kasus UMKM di Desa Sumber Arum Kecamatan Sukaraja Kabupaten Seluma) - Fitri Madyani; Idwal B; Yunida Een Fryanti (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Advances in digital technology, especially in payment systems, have provided convenience for Micro, Small, and Medium Enterprises (MSMEs). One innovation that plays a major role in this convenience is QRIS (Quick Response Code Indonesian Standard), which enables non-cash transactions practically and efficiently. However, in Sumber Arum Village, Sukaraja District, Seluma Regency, although some MSMEs already know about QRIS, the understanding and application of this technology in daily business activities is still relatively low. As a form of community service activity, the implementing team held socialization and training on the use of QRIS for local MSMEs. This activity lasted for one day and was attended by 13 out of 15 invited participants, with a participation rate of 86.67%. In this training, participants were given material presentations and direct practice on how to create a QRIS account and its use in transactions. Based on the evaluation results, all participants (100%) showed an increase in understanding regarding QRIS. Of the number of participants, 5 people succeeded in creating a QRIS account, and 3 of them had started using QRIS in their business transactions. This finding proves that even though the training was conducted in a short time, the right educational approach was able to increase digital literacy and encourage the implementation of technology among MSMEs in rural areas.